Which type of obesity benefits most from endoscopic intragastric balloon application? - Şahin, Azad Gazi; Alçı, Erman (The European Research Journal, 2025)
Objectives: As obesity poses significant health risks, exploring minimally invasive treatments like intragastric balloons becomes crucial for enhanced accessibility and efficacy in managing this pervasive public health challenge. This retrospective study aimed to evaluate the effectiveness of Intragastric Balloon (IGB) application in weight reduction across various degrees of obesity, providing a comprehensive assessment of its efficacy. Methods: A total of 187 patients with a BMI >30 kg/m2 underwent IGB application and were categorized into three groups based on the degree of obesity. Statistical analyses were conducted to assess weight loss, excess weight loss, and BMI reduction, focusing on the impact of IGB therapy in different degrees of obesity. Results: IGB application demonstrated significant efficacy in weight reduction across all degrees of obesity. Notably, the highest rates of excess weight loss were observed in patients with Class 1 obesity. Gender-specific analysis revealed variations in the response to IGB therapy, with females exhibiting higher success rates. Conclusions: The findings of this study highlight the efficacy of IGB application in achieving weight loss, emphasizing its effectiveness across different degrees of obesity. The notable success in Class 1 obesity underscores the potential of IGB as an effective treatment modality.